O Jednem w perspektywie filozoficzno-religijne - Karpiński, Maciej (Poznańskie Studia Teologiczne, 2010)
The One is the identity of Transcendens-Immanens. Far (external) as Transcendens, It becomes close (internal) as Immanens. This closeness entitles us to try to express the One. Reason, will and - involving both, in sacrum area - faith can testify of the One. It is previous to every philosophical discourse, which is asking about the principle of universe (arche). The One is previously given and - at least implicite - present in discourse. It is also, exactly as arche, the completion of this discourse. In the philosophy, which starts from and completes on the One, we can see the structural conflict between dualistic form of principium rationis and the trend to unity. However, this conflict seems to be the strength of the philosophy, when it assumes the positive shape of balance between rationality and extrarationality (existence). The One cannot be comprehended in rational way, because principium rationis invariably imposes to consider the One in contrast to multiplicity. „The One” in such understanding is not Transcendens (-Immanens), while entangled in dualism. Only in the symbiosis of rational and existential orders (thanks to mentioned balance) the One can overcome the rational determinateness. Then It reveals itself in eschatological dimension as Deity; the philosophical space becomes the religious space. Mystical experience takes place of meditation, becoming a kernel of faith - ultimate care. The commonness of ultimate care experience, which is known by every man, tends to stand for mystical egalitarianism, which means recognition of mystical state as the experience inherent connected with the human fate. As an expression of Transcendens-Immanens, the One calms. The One is a password (word of passing) ciphering arche of philosophy and Deity of religion. Reading of this cipher requires the cooperation of reason and existence - thinking and participation.